TANGGUNG JAWAB PEMERINTAH KOTA PALU TERHADAP PENGELOLAAN LINGKUNGAN PADA SEKTOR PARIWISATA - Idris; Jalaludin; Insarullah (TADULAKO MASTER LAW JOURNAL, 2024)
The research aims to find out how the responsibility of the Palu government is in managing the environment in the tourism sector, knowing the role of using environmental permit documents in the process of preserving, managing, and monitoring the environment in Palu carried out by business actors in the tourism sector. This research is a normative doctrinal legal research which emphasizes the understanding and study of primary legal materials in the form of legal principles and rules such as laws and regulations and provisions relating to the scope of the problems encountered. The research gathered the data at the Environmental Services Office and Tourism Office Palu. The results of the research show that there are three responsibilities of the government in managing the environment, namely: (1) As a construction maker for implementing environmental management, (2) As a regulator for implementing environmental management, (3) Involving the community directly in managing the environment. Moreover, the role of permit documents is also needed as a form of environmental management and monitoring efforts (UKL-UPL) which has been regulated in Law no. 32 of 2009. Based on the results of the discussion, it can be concluded that environmental management in the tourism sector and its implementation still refers to administrative compliance so that the activities carried out reflect environmentally friendly tourism activities. Based on this, the suggestions that can be given in this research, mainly for the government is to prove its roles and responsibilities in implementing regulation so as not to deviate from existing regulations, both the implementation of permits and compliance in the implementation of the provisions in the implementation of tourism activities in Palu which are in direct contact with environment.